Upaya Mengatasi Kesenjangan Sosial Di Sekolah Dasar Dalam Perspektif Teori Konflik Karl Marx - Nadya Aulia Sari; Zalfa Zahirah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article examines social inequality in elementary schools through the perspective of Karl Marx's conflict theory. The purpose of this study is to identify the causes of social inequality in elementary education and to formulate relevant solutions based on Marx's thinking. The method used is a qualitative descriptive approach. The results of the study show that educational inequality is caused by several factors, such as limited facilities and infrastructure, low quality of educators, and high education costs. The results of the study suggest strategic steps to reduce this inequality, namely equal access to education through financial assistance and fair distribution of resources, increasing teacher competence, especially in disadvantaged areas, and developing an inclusive and relevant curriculum for all levels of society. In addition, it is important to create a harmonious school environment that is free from socio-economic discrimination, so that every student feels valued and has the same opportunity to develop.